Rethinking Stress in Parents of Preterm Infants: A Meta-Analysis - Schappin, Renske; Wijnroks, Lex; Uniken Venema, Monica M. A. T.; Jongmans, Marian J. (PLOS ONE, 2013)
Background With improved medical outcome in preterm infants, the psychosocial situation of their families is receiving increasing attention. For parents, the birth of a preterm infant is generally regarded as a stressful experience, and therefore many interventions are based on reducing parental stress. Nevertheless, it remains unclear whether parents of children born preterm experience more stress than parents of term-born children, which would justify these interventions. This meta-analysis provides a comprehensive account of parental stress in parents of preterm infants, from birth of the infant through to their adolescence. Mean levels of stress in specific domains of family functioning were investigated, and stress levels in parents of preterm and term infants, and fathers and mothers of preterm infants, were compared. Furthermore, we investigated moderators of parental stress. Methods and Findings A random-effects meta-analysis was conducted including 38 studies describing 3025 parents of preterm (<37 wk) and low birth weight (<2500 g) infants. Parental stress was measured with two parent-reported questionnaires, the Parenting Stress Index and the Parental Stressor Scale: Neonatal Intensive Care Unit. The results indicate that parents of preterm-born children experience only slightly more stress than parents of term-born children, with small effect sizes. Furthermore, mothers have slightly more stress than fathers, but these effect sizes are also small. Parents report more stress for infants with lower gestational ages and lower birth weights. There is a strong effect for infant birth year, with decreasing parental stress from the 1980s onward, probably due to increased quality of care for preterm infants. Conclusions Based on our findings we argue that prematurity can best be regarded as one of the possible complications of birth, and not as a source of stress in itself.